Coaching as a Buffer for Organisational Change - Huflejt-Łukasik, Mirosława; Jędrzejczyk, Jan; Podlaś, Piotr (Frontiers in Psychology, 2022)
When introducing changes to an organisation, it is crucial to know how a given change will affect the company’s success. It is easy to forget or, more frequently, fail to appreciate the importance of the feelings and thoughts of the people who experience such changes. The distinction between objective change and subjective change is helpful in understanding the psychological consequences of changes and how they may affect the effectiveness of introducing changes in organisations. Results of studies on the psychological costs of changes for an individual indicate that there are differences in the way people experience objective and subjective changes, and that the way a change is perceived by an individual (i.e. subjective change) is crucial for the consequences of change. Studies have also identified factors which can buffer the negative consequences that changes may have on an individual. For changes in an organisation, coaching is one method to nurture these buffering factors in affected individuals, and, most of all, in those who are responsible for planning and introducing the changes, so that the employees of a company can experience the change in the most constructive way possible.